2019
DOI: 10.1017/s0031182019000325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some natural products from fungal and herbal sources on Giardia lamblia in vivo

Abstract: Giardia lamblia (G. lamblia) is the most widely known protozoan parasite that causes human gastrointestinal infection worldwide. Some natural compounds exhibited pivotal effects against different infectious diseases. In this research, the antigiardial activity and cytotoxicity of fungal chitosan, nano-chitosan, Rhamnus cathartica (R. cathartica) and emodin were evaluated in Balb/c mice. Genotyping of G. lamblia was assessed by PCR-RFLP technique. Different concentrations of mentioned compounds were used to che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…After the incubation time, the supernatant was removed and 100 μL of DMSO was added. Finally, we measured the absorbance at 570 nm (20 This increase is dependent on concentration and time, and with the increase in the concentration and treatment time in both cell lines, the cell viability decreases. Additionally, the results revealed the greater sensitivity of the cancer cells to the extract.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the incubation time, the supernatant was removed and 100 μL of DMSO was added. Finally, we measured the absorbance at 570 nm (20 This increase is dependent on concentration and time, and with the increase in the concentration and treatment time in both cell lines, the cell viability decreases. Additionally, the results revealed the greater sensitivity of the cancer cells to the extract.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the effects of this drug, viability tests are usually used. To evaluate the toxicity and liver enzymes, such as ASL, ALT and ALP, cell culture is normally used(5, [15][16][17]. The current study aimed to evaluate the effects of E. camaldulensis hydroalcoholic extract on the human lung cancer cell line and analyze its antibacterial and antiviral properties.…”
mentioning
confidence: 99%
“…J774 cell lines (2 × 10 4 cells) were seeded in 96-well plates and incubated at 37 °C for 24 h. In order to remove the unattached cells, the supernatants were removed and replaced with fresh RPMI 1640 medium containing 100 μL of 2.5, 5, 10, 25, 50 and 100 μg/mL of ART, NLCs, ART-NLCs, and AMB and then incubated at 37 °C with 5% CO 2 for 24 and 48 h. Untreated cells were chosen as the negative control. The cell viability and cell cytotoxicity were determined by MTT colorimetric test ( 26 )and was calculated using the equations below:…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Chabra et al (2019) reported that chitosan and nanochitosan at the concentrations of 100, 200, and 400 µg/ml significantly reduced the G. lamblia trophozoite, ranging from 89 to 100, after 3 h exposure in vitro. The findings also showed that the oral administration of chitosan and nano-chitosan at the dose of 100 µg/kg significantly reduced the mean percentage of excreted cysts up to 10 times in the infected BALB/C mice G. lamblia [14].…”
Section: Chitosanmentioning
confidence: 99%